2017
DOI: 10.3847/1538-4357/aa8dfd
|View full text |Cite
|
Sign up to set email alerts
|

Type I Shell Galaxies as a Test of Gravity Models

Abstract: Shell galaxies are understood to form through the collision of a dwarf galaxy with an elliptical galaxy. Shell structures and kinematics have been noted to be independent tools to measure the gravitational potential of the shell galaxies. We compare theoretically the formation of shells in Type I shell galaxies in different gravity theories in this work because this is so far missing in the literature. We include Newtonian plus dark halo gravity, and two non-Newtonian gravity models, MOG and MOND, in identical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…velocity would drop substantially between pericentres (Vakili et al 2017). A more uniform distribution of shell radii would be expected in the absence of CDM, which is broadly more in line with observations of NGC 3923 (Bílek et al 2016).…”
Section: Shell Galaxiessupporting
confidence: 81%
See 1 more Smart Citation
“…velocity would drop substantially between pericentres (Vakili et al 2017). A more uniform distribution of shell radii would be expected in the absence of CDM, which is broadly more in line with observations of NGC 3923 (Bílek et al 2016).…”
Section: Shell Galaxiessupporting
confidence: 81%
“…The use of shells to test MOND was discussed further in Bílek et al (2015a) and Vakili et al (2017), with the latter authors also considering MOG (subsequently falsified in Figure 11). In general, the strong dynamical friction expected in the ΛCDM scenario suggests that large faint shells should be accompanied by small bright shells because the launch Table 2.…”
Section: Shell Galaxiesmentioning
confidence: 99%
“…When integrated backwards, the orbits of the Large and Small Magellanic Clouds were close to pericenter almost when the MW and M 31 were at the pericenter. Dynamical friction during encounters of comparable galaxies is known to be weaker in MOND than in ΛCDM from the simulations by ; Nipoti et al (2008); Combes (2016) (see also, Renaud et al 2016or Vakili et al 2017 because of the absence of the large and massive dark matter halos (Kroupa 2015). A close MW-M 31 encounter in MOND would therefore be more likely to avoid ending in a merger than in ΛCDM.…”
Section: Introductionmentioning
confidence: 96%
“…Dynamical friction considerations have often been used to constrain dark matter properties, such as dark halo density profiles through requiring the survival of observed globular clusters in dwarf spheroidal galaxies (e.g. Hernandez & Gilmore 1998, Goerdt et al 2006, the consistency of the observed morphology of shell galaxies in dark matter models (Vakili et al 2017), the merger dynamics of forming galaxies (Peñarrubia et al 2002, Kroupa 2015 or the survival of ultra-faint dwarf galaxies (Hernandez 2016). In terms of future tests, Pani (2015) showed that dynamical friction on binary pulsars detected close to the galactic centre could also yield interesting restrictions.…”
Section: Introductionmentioning
confidence: 99%